Google Classroom as a Distance Learning Media: Limitations and Overcoming Efforts - Suparjan Suparjan; Mariyadi Mariyadi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study investigates the obstacles that teachers faced using Google Classroom as a platform for Distance Learning (PJJ) during the COVID-19 pandemic at the elementary school level. This study also examines how elementary school teachers overcome the obstacles they experience while conducting distance learning through Google Classroom. This type of research is descriptive qualitative research. In-depth semi-structured interviews were used to collect data from 8 teacher respondents who actively use Google Classroom in teaching activities in Pontianak. The findings indicate that the obstacles faced by teachers during learning activities are limited facilities and infrastructure, lack of technical support, difficulties in controlling students, and lack of human resources. Teachers have made maximum efforts to overcome these obstacles by utilizing available facilities and infrastructure and affordable technical support and organizing independent training activities and peer-to-peer tutorial activities related to distance learning, such as controlling student learning and improving human resources quality.